Makusam Yogurt and Child Pose Yoga for Dysmenorrhea Management - Antri Ariani Antri; Yanyan Mulyani; Iceu Mulyati; Intan Yusita (LP2M INSURI Ponorogo, 2026)
Dysmenorrhea is a prevalent reproductive health concern among adolescent girls that may disrupt everyday activities, school participation, and concentration. This community service initiative sought to strengthen adolescents' understanding of non-pharmacological care for dysmenorrhea through Makusam Yogurt—prepared with yogurt, honey, turmeric, and tamarind—and Child's Pose yoga, while also reducing menstrual pain. A training-based community intervention with a one-group pretest–posttest design was conducted among 52 adolescent girls in the service area of Solokan Jeruk Public Health Center, Bandung Regency. Activities comprised reproductive health education, hands-on preparation of Makusam Yogurt, guided Child Pose practice, and outcome assessment using a knowledge questionnaire and the Numeric Rating Scale (NRS). Following the program, the proportion of participants classified as having good knowledge rose from 60% to 85%. Moderate menstrual pain declined from 68% before the intervention to 5% afterward, and participants were able to prepare Makusam Yogurt independently. The findings suggest that combining health education, an herbal functional-food innovation, and a simple yoga exercise offers a practical and potentially sustainable approach to improving reproductive health knowledge and alleviating dysmenorrhea among adolescent girls.